Empowerment tuberculosis cadres with participatory socialization as effort to improve the TB suspect's achievements at the Sempu’s Public Health Center - SEPTIYANINGSIH, NANDA EKA PUTRI; MANDAGI, AYIK MIRAYANTI; RAMADHAN, SYAHRUL; PUTRI SEPTIANINGRUM, SHINTA TRI ANANDA (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Background: Tuberculosis (TB) is an infectious disease with high mortality and morbidity rates in Indonesia, caused by the bacterium Mycobacterium tuberculosis. The Case Detection Rate (CDR) in Banyuwangi is still relatively low at 54% compared to the set target. In Banyuwangi, one of the Non-Governmental Organizations (NGOs), Yayasan Bhanu Yasa Sejahtera Yabhysa, supports the TB control program in the region. Since 2021, this community has collaborated with the Banyuwangi Health Department to implement community-based TB interventions in 28 Community Health Centers (Puskesmas) spread across 16 districts, with a total of 66 active TB cadres. The aim of this community service is to train Tuberculosis (TB) cadres through socialization to improve the performance of TB suspects in Sempu Banyuwangi Community Health Center. Methods: The analysis of knowledge improvement data used a paired T-test with a 95% Confidence Interval. The test was conducted to evaluate the difference in knowledge improvement before and after education. Results: From the results of this community service, there was an increase in knowledge before and after socialization by 0.06 or 6%. The formation of TB cadres through contact investigation simulation carried out in community service activities resulted in the formation of four cadres. Conclusion: Based on the pre-test and post-test results, respondents showed a 6% increase in knowledge. The hope of this community service is to improve the achievement of TB suspect cases and reduce TB cases in Sempu Community Health Center.